2019
DOI: 10.4018/ijskd.2019100102
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media in Education and Using Social Media Strategies in Education and Corporate Organizations in the U.S. and Belarus

Abstract: Rapid growth of new media technologies allows organizations to communicate with consumers in immediate and interactive ways via blogs and social media websites such as Facebook and Twitter. Consumers, companies, and organizations bypass mass media gatekeepers and engage in direct communication exchanges. This study examines social media efficacy from the perspective of corporate and educational organizations in the United States and Belarus. Using the Delphi method, authors administered iterative surveys to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The results showed that social media adoption in higher education institutions positively impacts leadership and knowledge revision. As Vilceanu, FitzGerald [ 6 ] discovered, social media allows leaders to stay current, including following experts for the latest information, participating in discussions, and visiting informed on developments. Second, leaders can share knowledge and establish reputations by publishing articles and content and engaging in discussions - positioning themselves as experts [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that social media adoption in higher education institutions positively impacts leadership and knowledge revision. As Vilceanu, FitzGerald [ 6 ] discovered, social media allows leaders to stay current, including following experts for the latest information, participating in discussions, and visiting informed on developments. Second, leaders can share knowledge and establish reputations by publishing articles and content and engaging in discussions - positioning themselves as experts [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the adoption of technology by HEIs is contingent on organizational strategy and differs among HEIs in the same education system [ 5 ]. The use of social media in education has drawn interdisciplinary interest [ 6 , 7 ] as HEIs shift communication from one-way to interactive to regularly engage stakeholders [ 8 ]. Continual society-wide communication needs frequent updates across media, especially social platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent lectures focus on problems students are still having after self-study of the material… (Bates & Galloway, 2012, p. 1). Simplisticallydefineditreferstoastudymethodologyinwhichstudentsdothehomeworkat schoolandtheschoolworkathome (McCrea,2016).Thispedagogicalapproachpermitsteachers/ instructorstomakeuseofacombinationofclassroommethodologiesaimedatcombininge-learning andclassroominstruction (Majumdar,2013;Momani,2020;Vilceanu,FitzGerald,&Sadovskaya, 2019;Mallek,Ghozzi,&Gargouri,2020).Suchablendisknowntobesuperiortotheindividual useofeithermethodology (Koller,2011).…”
Section: Flipped Classroommentioning
confidence: 99%